Markups of Exporters and Importers: Evidence from Hungary - Cecilia Hornok; Balázs Muraközy (Scandinavian Journal of Economics, 2019)
This paper studies the relationship between different proxies of firm-level markups and trade status using balance sheet information linked to detailed trade data from Hungary between 1995-2003. We find that importing is strongly positively correlated with markup measures both across and within firms. We argue that this correlation can reflect three channels: self-selection, higher physical productivity resulting from access to a larger variety of inputs and quality upgrading based on high-quality imported intermediate inputs. We present evidence for the relevance of the latter channel by showing that importers' markup premium is higher when inputs arrive from developed countries and that importing is correlated with higher quality (price-adjusted revenue) exports. We find no robust evidence for exporter premium when controlling for importing. We argue that the nonexistent exporter premium may result from the stronger competition in export markets relative to domestic ones.
Keywords: D22; D24; F14; L11; L60; 330; markup premia; detailed trade data; quality; self-selection